FTIR synchrotron spectroscopy of the S–H stretching fundamental of the 12CH332SH species of methyl mercaptan. (17th December 2018) - Lees, R. M.; Xu, Li-Hong; Twagirayezu, S.; Perry, D. S.; Dawadi, M. B.; Billinghurst, B. E.
ABSTRACT: The infrared Fourier transform spectrum of the S–H stretching fundamental band of 12 CH3 32 SH has been recorded using synchrotron radiation at the far-infrared beamline of the Canadian Light Source in Saskatoon. The S–H stretch is a hybrid band predominantly of perpendicular b -type with a small parallel a -component. With both Δ K = +1 and Δ K = −1 sub-bands present, the assignments are well determined from ground-state combination difference relations. The identified sub-bands access S–H stretching ground torsional substates from K′ = 0–14 for A and E torsional species. The substate origins have been obtained by expanding the term values in J ( J + 1) power series, and have been fitted to a simple 6-parameter Fourier Hamiltonian to deduce the torsional energies. The oscillation amplitude of the S–H stretching torsional curves is 0.547 cm − 1 compared to 0.653 cm − 1 for the ground state, implying an increase on the order of 6.9% in the torsional barrier height. The vibrational wavenumber for the S–H stretch mode is found to be 2603.5 cm − 1 . GRAPHICAL ABSTRACT: